Total Safety Management: What are the Main Areas of Concern in the Integration of Best Available Methods and Tools - M.C. Leva; N. Balfe; T. Kontogiannis; E. Plot; M. Demichela (Chemical Engineering Transactions, 2014)
“BP released findings from its own internal investigation of the oil spill in the Gulf of Mexico, revealed inefficient Organization interfaces among BP management, the rig crew and well site leader. Also according to the investigation, one important contributor to the accident was inadequate guidelines for critical tests and operations”. (Pires and Mosleh 2011) Over the recent past, the accumulation of major mishaps, crises and accidents have made it clear that organisations must still improve their capabilities to address safety “not as a stand-alone activity that is separate from the main activities and processes of the organization” but as an integrated part of total performance management. The requirements for safety management in existing and upcoming standards and regulations, as for example the ISO 31000 and or the Seveso II directive, call for a proactive strategic approach, anticipating risks and demonstrating a capacity to keep safety at the centre of changes driven by commercial competition, and ensuring that safety evidence itself becomes an effective driver of change. However there is often a gap between the state principles and an actual roadmap to their implementation. Furthermore organisations, especially the one dealing with safety critical operations, find it difficult to integrate their different functional units in a common programme of operations management or change; there is no clear consensus about what it means to be ‘proactive’; there is no integrated framework for analysing or managing all the human related functions in an operational system. Innovation may rely on assembling the best practices, tools and methods already available for functional analysis, risk assessment, interactive emergency scenarios analysis, performance monitoring, design review, training and knowledge management, in an integrated framework able to address safety management in the main aspects of a product or process lifecycle the cornerstone of which is the building of a common operational picture to support the capacity to perform more participatory and dynamic risk identification and solutions loops in: Design (new plants, processes /procedures availing new visualization tools) Ad hoc critical activities (management of change or scheduled overhaul) Operations management (establishing of dynamic risk registers). This is the scope of a new EU funded research project called TOSCA and the present paper will introduce the current framework being built.